Chemotherapy and repeat resection abrogate the prognostic value of neutrophil lymphocyte ratio in colorectal liver metastases. Issue 5 (May 2020) - Hand, Fiona; Ryan, Elizabeth J.; Harrington, Cuan; Durand, Michael; Maguire, Donal; O'Farrelly, Cliona; Hoti, Emir; Geoghegan, Justin G.
Abstract: Background: Evolution in surgical and oncological management of CRLM has called into question the utility of clinical risk scores. We sought to establish if neutrophil lymphocyte ratio (NLR) has a prognostic role in this patient cohort. Methods: From 2005 to 2015, 379 hepatectomies were performed for CRLM, 322 underwent index hepatectomy, 57 s hepatectomies were performed. Clinicopathological data were obtained from a prospectively maintained database. Variables associated with longterm survival following index and second hepatectomy were identified by Cox regression analyses and reviewed along with 30-day post-operative morbidity and mortality. Results: Following index hepatectomy 1-, 3-and 5-year survival was 90.7%, 68.1% and 48.6%. Major resection, positive margins and >5 tumours were negatively associated with survival. Those with elevated NLR(>5) had a median survival of 55 months, compared to 70 months with lower NLR(p = 0.027). Following neoadjuvant chemotherapy, no association between NLR and survival was demonstrated (p = 0.93). Furthermore, NLR >5 had no impact on prognosis following repeat hepatectomy. Tumour diameter >5 cm (p = 0.04) was the sole predictor of poorer survival (p = 0.049). Conclusion: Despite elevated NLR correlating with shorter survival following index hepatectomy, this effect is negated by neoadjuvant chemotherapy and second hepatectomy for recurrent disease. This data would not support the use of NLR in the preoperative decision algorithm for patients with CRLM.